The Study of Combination Ethanol Extract of Averrhoa bilimbi L. and Momordica charantia L. on CD4+CD25+TGF-β+ Spleenocytes of Hyperglycemia Mice - Amrulloh, Harits; Novinda, Bella; Sartika, Intan; Widyarti, Sri; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2020)
Diabetes mellitus is one of the four priority non-infectious diseases in the world. Plant-based medicine is an alternative treatment with few side effects. Star fruit (Averrhoa bilimbi L.) and bitter melon (Momordica charantia L.) are plants that have anti-hyperglycemic activity. Hyperglycemia produces Reactive Oxygen Species (ROS) that make the β-cells of the pancreas necrosis that decreasing insulin synthesis. The anti-inflammatory activity appears based on the relative levels of CD4+ and CD25+, which are TGF-β-producing regulatory T cells where TGF-β is a mediator that acts as an immunosuppressant. TGF-β would induce CD4 + T lymphocytes into T reg. The purpose of this study is to determine the profile of TGF-β on CD4+ and CD25+ spleenocytes on hyperglycemia mice after ABMC (Averrhoa bilimbi Momordica charantia mix) treatment. Mice were divided into 5 groups, non-diabetic (N), hyperglycemia (H), hyperglycemia with extract doses of 10 mg.kg-1 BW (P1), 40 mg.kg-1 BW (P2), and 160 mg.kg-1 BW (P3). Diabetic mice were obtained after a single injection dose of 145 mg.kg-1 BWÂ streptozotocin (STZ). The result showed that ABMC can reduce blood sugar levels faster and able reduce the number of CD4+TGF-β+ cells in hyperglycemia mice. Keywords: Averrhoa bilimbi L., CD4+TGF-β+, CD25+TGF-β+, hyperglycemia, Momordica charantia L.